2013 IEEE 4th International Conference on Electronics Information and Emergency Communication 2013
DOI: 10.1109/iceiec.2013.6835462
|View full text |Cite
|
Sign up to set email alerts
|

Serial concatenation of quadratic interleaved codes in different wireless doppler environments

Abstract: Abstract-The remarkable development of mobile networks has enabled ubiquitous communications that has transformed the way people connect with each other. Meanwhile, the growing adoption of smartphones, tablets, and increasingly bandwidthintensive applications and services is driving unprecedented mobile broadband traffic growth; therefore, finding state-of-theart strategies for improving the wireless transmission reliability has emerged significantly. In particular, to enable significant mitigation of the detr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 41 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…It has been previously shown that serial turbo‐like codes employing the quadratic permutations (QPs), that is, the serial concatenation of quadratic interleaved codes (SCQICs), result in outstanding coding gains [3–6]. This paper aims to supplement and extend the pivotal system design guidelines of our previous works in order to achieve a flexible SCQIC framework in terms of other crucial contradictory performance factors, so as to address the proposed SCQICs in cooperation with the highly matured technologies (e.g.…”
Section: Research Contributionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been previously shown that serial turbo‐like codes employing the quadratic permutations (QPs), that is, the serial concatenation of quadratic interleaved codes (SCQICs), result in outstanding coding gains [3–6]. This paper aims to supplement and extend the pivotal system design guidelines of our previous works in order to achieve a flexible SCQIC framework in terms of other crucial contradictory performance factors, so as to address the proposed SCQICs in cooperation with the highly matured technologies (e.g.…”
Section: Research Contributionmentioning
confidence: 99%
“…The selected half‐rate outer SRCC trellis structures for r ≤ 0.33 and L ≤ 5 are tabulated in Table 1. The interleaver applies the QP on the bit sequences obtained from the previous step, which is originally proposed in [12, 13] and further developed for serial turbo‐like codes in [3–6]. Let x oc.…”
Section: Wireless System Modelmentioning
confidence: 99%
See 3 more Smart Citations